La somiglianza come induttore causale (Comparatismi, 2025)
Recent studies on magical thinking by English psychologist Eugene Subbotsky and a recent study conducted at the University of Modena and Reggio Emilia demonstrate how Homo sapiens has inherited a cognitive bias whereby similar elements tend to be interpreted as the cause of one another, making isomorphism a genuine causal inducer. Rather than being a vestige of childhood or archaic times, neurocognitive studies provide compelling evidence that isomorphism helps us interpret reality according to classificatory systems that often do not diverge from scientific logic, and that counterfactuality in particular (whether fairy tales or science fiction) constitutes not only a testing ground for causal logic but also an activator of creativity.
Keywords: Isomorphism; Magical thinking; Causal logic; Metonymy; Anthropomorphism